(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Marine Geology is one of the most recently developed branches of the geological sciences, which began to actively evolve after the mid XX century when the “modern” research techniques for obtaining really trustworthy data from the ocean floor and subbottom appeared, such as high resolution bathymetry, seismic, sea-bottom profilers, submarine photography and sea-floor sampling. In the Southwestern Atlantic continental margin the first great impulse occurred in the 1950´s and 1960´s by the agreement achieved between the Lamont-Doherty Earth Observatory (LDEO) of the Columbia University (USA) and the Argentina Hydrographic Survey (SHN). It was a pioneering work at a global scale as it represented a leading case for developing marine seismic technologies at sea useful for understanding the major oceanic sedimentary processes and the subbottom structure (e.g., Ahrens et al., 1971). Also in the 1960’s, another major agreement between CONICET (Argentina) and Woods Hole Oceanographic Institution (USA) allowed the acquisition by the Argentine government of the former research vessel Atlantis (later named, under Argentine flag, as “El Austral” and presently “Dr. Bernardo Houssay”), which was the first ship specifically built for oceanographic research and one of the most famous and internationally recognized because of its contribution to the knowledge of the ocean floors between 1939 and the latest 1950´s, including the findings that initially supported the continental drift´s theory. Following that, several national initiatives helped to advance in the development of marine geological sciences in the region. Among the most important we can mention: the REMAC Project in Brazil in the 1960’s and 1970’s -that allowed the participation of several Brazilian universities as well as North American research institutions-, the agreement between the SHN and the Uruguayan Oceanographic, Hydrographic and Meteorological Survey (SOHMA) in the 1970 ´s and 1980´s under the framework of the Administrative Commission for the Río de la Plata (CARP), the agreement between SOHMA and the Rio Grande do Sul University (URGS, Brazil) in the 1980´s and 1990´s, and the Projects MARGEN in Argentina and REVIZEE in Brazil - that began in the 1980´s-. The highly significant results that arose from those agreements and national projects impulsed the Argentina-Brazil-Uruguay geological communities to focus on the importance of deeply studying the ocean environments in the region and the needs to organize working teams aimed at developing research programs on the subject.